Association between the neutrophil-to-lymphocyte ratio and cognitive impairment: a meta-analysis of observational studies - Hung, Kuo-Chuan; Liu, Chien-Cheng; Wu, Jheng-Yan; Ho, Chun-Ning; Lin, Ming-Chung; Hsing, Chung-Hsi; Chen, I-Wen (Frontiers in Endocrinology, 2023)
Background: Systemic inflammation is one of the underlying mechanisms of cognitive impairment. The neutrophil-to-lymphocyte ratio (NLR) has emerged as a systemic inflammation indicator. This meta-analysis aimed to evaluate the association between high NLR and cognitive impairment (CI) risk.: A comprehensive systematic search was conducted to identify eligible studies published until May 30, 2023. The reference group comprised patients with the lowest NLR level, whereas the exposure group comprised those with the highest NLR level. The main outcome was to examine the relationship between NLR and CI risk. The secondary outcome included the association between patient characteristics or comorbidities and CI risk.Results: This meta-analysis included 11 studies published between 2018 and 2023, involving 10,357 patients. Patients with CI had a higher NLR than those without (mean difference=0.35, 95% confidence interval [CI]: 0.26-0.44, p < 00001, I 2 = 86%). Consistently, pooled results revealed an association between high NLR and CI risk (odds ratio [OR]=2.53, 95% CI:1.67-3.82, p<0.0001, I 2 = 84%). Furthermore, aging (mean difference =4.31 years, 95% CI:2.83-5.8, p < 0.00001, I 2 = 92%), diabetes (OR=1.59, 95% CI:1.35-1.88, p < 0.00001, I 2 = 66%), and hypertension (OR=1.36, 95% CI:1.19-1.57, p < 0.00001, I 2 = 0%) were significant risk factors for CI. However, no significant associations were observed between CI and male gender (OR = 0.84, 95% CI:0.64-1.11, p = 0.22, I 2 = 81%), body mass index (mean = −0.32 kg/m 2 , 95% CI: −0.82, 0.18, p = 0.2, I 2 = 82%), alcohol consumption (OR = 1.11, 95% CI:0.95−1.3, p = 1.35, I 2 = 0%), and smoking (OR = 0.99, 95% CI:0.87-1.13, p = 0.86, I 2 = 0%). Meta-regression found that diabetes and hypertension, but not age, significantly moderated the association between NLR and CI.This meta-analysis showed a significant association between high NLR and increased CI risk. Moreover, meta-regression identified diabetes and hypertension, but not age, as significant moderating factors in the relationship between NLR and CI. To validate and strengthen these findings, further large-scale studies are required.